BIOACTIVE POTENTIAL OF AN EPIBIOTIC STREPTOMYCES STRAIN, CN3 FROM THE SEA FAN JUNCELLA JUNCEA - C, CHELLARAM; John A, Alex (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: To screen and isolate peptide antibiotics producing epibiotic bacteria from the surface of the sea fan Juncella juncea, and partially purify the active compound. Methods: In this study, epibiotic bacteria were isolated by swabbing a small area of the coral surface with a sterile cotton swab, which was then directly swabbed on to Zobell marine agar plates. Antibiotic production was screened using agar overlay method and the active peptide was partially purified using anion exchange chromatography and reversed phase high-performance liquid chromatography (RP-HPLC). Phylogenetic identification based on comparative sequence analysis of 16Ss rRNA gene indicated that the stain fell under the genera Streptomyces. Results: In the initial screening using agar overlay method the strain was found to exhibit broad spectral activity exhibiting both antibacterial and antifungal activities. Protease digestion of the crude extract resulted in the loss of activity indicating the proteinaceous nature of the active molecules. Bioassay guided purification using anion exchange chromatography, and RP-HPLC was carried and the active peptide was partially purified. An epibiotic Streptomyces strain CN3 producing potent broad spectral peptide was isolated. Conclusion: This study highlights the importance of epibiotic bacteria associated with corals as a potential source for the discovery of novel antimicrobials and other natural products. Keywords: Coral, Matrix-assisted laser desorption/ionization time-of-flight, Selected pathogens.